2018
DOI: 10.1002/jper.17-0653
|View full text |Cite
|
Sign up to set email alerts
|

Vibration enhances PGE2, IL‐6, and IL‐8 expression in compressed hPDL cells via cyclooxygenase pathway

Abstract: Mechanical vibration may enhance alveolar bone resorption at the compression side during orthodontic tooth movement via a mechanism involving the cyclooxygenase pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…Our previous studies demonstrated LMHF vibration upregulated COX-2, PGE2, IL-6, IL-8 and RANKL, and further increased the levels of these osteoclastogenic factors in compressed PDL cells. 10,11 In addition, we found that the cyclooxygenase pathway is required to induce IL-6 and IL-8 in compressed PDL cells either compressive stress alone or in combination with vibration. On the other hand, the expression of IL-6 and IL-8 in response to vibration alone is the cyclooxygenase pathway independent.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Our previous studies demonstrated LMHF vibration upregulated COX-2, PGE2, IL-6, IL-8 and RANKL, and further increased the levels of these osteoclastogenic factors in compressed PDL cells. 10,11 In addition, we found that the cyclooxygenase pathway is required to induce IL-6 and IL-8 in compressed PDL cells either compressive stress alone or in combination with vibration. On the other hand, the expression of IL-6 and IL-8 in response to vibration alone is the cyclooxygenase pathway independent.…”
Section: Discussionmentioning
confidence: 80%
“…This concentration was previously reported as an effective dose. 6,11 Samples were collected for analysis immediately after the experiments ended. The expression of RANKL and OPG were analysed using quantitative real-time polymerase chain reaction (qPCR).…”
Section: Application Of Mechanical Stress and Cox-2 Inhibitormentioning
confidence: 99%
See 1 more Smart Citation
“…Vibratory stimulus has been proposed as an approach to accelerate tooth movement . In vitro studies suggest vibration may accelerate tooth movement by inducing inflammatory mediators, though animal studies have reported conflicting results and vibration did not accelerate irregularity index improvements in clinical studies . Nevertheless, the ability of vibration to increase the distance of tooth movement is controversial .…”
Section: Introductionmentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ periodontal tissue injury [11][12][13] . Thus, methods to control the inflammatory response and to eliminate periodontal bacteria are considered to be important for the inhibition of periodontal disease.…”
mentioning
confidence: 99%